PHESE CHARACTERISTICS VARACTORS MULTIPLIERS OF FREQUENCY - A. I. Logvin; E. A. Lutin (Научный вестник МГТУ ГА)
Described connection betwttn phase and amplitude characteristics of varactors multipliers frequency with change mode operation of devices.